Application of 3D printing and its various technologies in dentistry - Al-Sharif, Rajeh M.; Althaqafi, Khaled A.; Alkathiry, Hend S.; Alzeer, Abdulrahman A.; Shareef, Raiya M.; Omran, Samia M.; Alabduljabbar, Zahra M.; Alnuman, Asmaa A.; Alshahrani, Abdullah M.; Alharbi, Abeer M.; Alqahtani, Saad H.; Alsharif, Haya T. (International Journal Of Community Medicine And Public Health, 2022)
Many applications for these technologies have been reported in multiple fields, including dentistry, within the last three decades. It can be used in periodontology, endodontics, orthodontics, oral implantology, maxillofacial and oral surgery, and prosthodontics. In the present literature review, we have discussed the different clinical applications of various 3D printing technologies in dentistry. Evidence indicates that 3D printing approaches are usually associated with favorable outcomes based on the continuous development and production of novel approaches, enabling clinicians to develop complex equipment in different clinical and surgical aspects. Developing work models to facilitate diagnostic and surgical settings is the commonest application of these modalities in dentistry. Besides, they can also be used to manufacture various implantable devices. Accordingly, they significantly help enhance the treatment process, reducing costs and less invasive procedures with favorable outcomes. Finally, 3D printing technologies can design complex devices in a facilitated and more accurate way than conventional methods. Therefore, 3D printing should be encouraged in clinical settings for its various advantages over conventional maneuvers.